Epidemiological profile of isolated bacteria in a public pediatric hospital - Alves, Geisa Cristina Silva; Paiva, Magna Cristina; Baldoni, André Oliveira; Sanches, Cristina (Revista de Epidemiologia e Controle de Infecção, 2020)
Background and objectives: In recent years the incidence of resistant bacteria has increased significantly and in Brazil there is little research on the subject regarding pediatric hospitals. Therefore, this study aimed to analyze the epidemiological profile of the main bacteria recovered from biological samples of a Brazilian pediatric hospital. Methods: This is a descriptive and retrospective study. The study was conducted over 24 months, based on reports of microbiological tests issued by the infection control service of a pediatric hospital located in the Center West of the Brazilian state of Minas Gerais. Results: A total of 4286 bacteria were recovered from biological samples, of which 1107 (25.82 %) were responsible for infections related to health care (IRHC) at the institution of origin. The main microorganisms identified were Pseudomonas aureuginosa, Acinetobacter baumannii, Staphylococcus aureus, Escherichia coli, and Klebsiella pneumoniae. Conclusion: The prevalence profile of the bacteria recovered from the biological samples was similar to the studies conducted internationally.